Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1007/s10208-007-9010-0
|View full text |Cite
|
Sign up to set email alerts
|

Convergence of the Magnus Series

Abstract: The Magnus series is an infinite series which arises in the study of linear ordinary differential equations. If the series converges, then the matrix exponential of the sum equals the fundamental solution of the differential equation. The question considered in this paper is: When does the series converge? The main result establishes a sufficient condition for convergence, which improves on several earlier results.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
108
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(109 citation statements)
references
References 18 publications
1
108
0
Order By: Relevance
“…Here we state a theorem which, on the one hand, explains the phenomena observed by Moan and Niesen [27] and, on the other hand, provides a new tool to determine the actual convergence domain of the Magnus series in some physically relevant examples and applications.…”
Section: Another Characterization Of the Convergence Of The Magnus Sementioning
confidence: 86%
“…Here we state a theorem which, on the one hand, explains the phenomena observed by Moan and Niesen [27] and, on the other hand, provides a new tool to determine the actual convergence domain of the Magnus series in some physically relevant examples and applications.…”
Section: Another Characterization Of the Convergence Of The Magnus Sementioning
confidence: 86%
“…Magnus [24] showed that the solution of the differential equation y = A(ξ)y can be written as y(ξ) = exp(Ω(ξ)) y(0), where the matrix Ω(ξ) is given by the infinite series [26] proved that the series converges if…”
Section: Magnus Methodsmentioning
confidence: 99%
“…In general, the Magnus series does not converge unless A is small in a suitable sense. Several improved bounds to the actual radius of convergence in terms of A have been obtained along the years [18,1,15,17]. In this respect, the following result is proved in [6]: This theorem, in fact, provides the optimal convergence domain, in the sense that π is the largest constant for which the result holds without any further restrictions on the operator A(t).…”
Section: Magnus Series and Its Convergencementioning
confidence: 99%